Mechanical Thrombectomy in Acute Ischaemic Stroke: A Review of the Literature, Clinical Effectiveness and Future Use - Lally, Frank; Grunwald, Iris Q.; Sanyal, Ranjan; Natarajan, Indira; Roffe, Christine (CNS & Neurological Disorders - Drug Targets, 2013)
The only effective treatment licensed for acute ischaemic stroke is intravenous thrombolysis within 4.5 hours from stroke onset. An alternative method of restoring blood flow is mechanical thrombectomy (MT). Although this is highly effective at recanalization, it remains unclear whether it is more effective than thrombolysis in improving clinical outcomes. This review examines key clinical outcomes from published studies and reviews ongoing studies to identify devices, patient population, and stated outcomes of MT. We discuss the issues when comparing clinical outcomes from different trials and suggest measures to help standardize reporting. We used routine review methodology to search relevant databases for stroke and MT published between 1999 - 2012 and active trials between August 2011 - May 2012. The studies in this review had an overall patient population of 8354. The most widely used primary outcome (94% of studies) was successful recanalization. The mean mortality across the studies was 17% (range 7 - 44), 64% of studies reported neurological improvement and 97% reported functional outcome with 42% (range 15 - 54)] achieving independence in activities of daily living. Mean symptomatic intracerebral haemorrhage was 11% (range 0 – 45%). There were significant differences in outcome reporting between studies. Evidence from published studies shows a strong relationship between recanalization and good outcomes although nonstandardization makes comparisons difficult. There is a trend towards higher recanalization, lower mortality, and better functional outcome in more recent studies. To examine effectiveness of MT vs thrombolysis, randomized controlled trials are needed. Several are currently in progress but it remains to be seen if procedures and outcomes are reported in a standardized manner.
Keywords: recanalization